Quality of life and posttraumatic growth after adult burn: A prospective, longitudinal study - Martin, L.; Byrnes, M.; Bulsara, M.; McGarry, Sarah; Rea, S.; Wood, Fiona (Pergamon Press, 2017)
© 2017 Elsevier Ltd and ISBI Posttraumatic growth is positive psychological change that occurs beyond pre-trauma levels. Understanding the relationship between growth, stress and quality of life after burn improves understanding about the nature of postburn psychological growth and associated quality of life factors. This study aimed to determine the nature of these relationships, and whether posttraumatic growth changed over time in individuals. Two hundred and seventeen surveys were collected from 73 adult burn patients. The Posttraumatic Growth Inventory, Depression, Anxiety and Stress Score, SF-36 quality of life and Burns Specific Health Score - Brief surveys, together with demographic and clinical information was collected over a six month period. Acute and non-acute burns were equally represented. Growth and stress were positively correlated (p = 0.004), but depression and growth had a curved relationship (p = 0.050). Growth scores reduced as affect (p = 0.008) and mental health improved (p < 0.0001), and were highest at mid-levels of physical recovery (p = 0.001). This supports the concept that PTG is linked to coping as higher growth is reported with more stress, and that depression is a barrier to growth. As patients recover both physically and mentally from burn, less growth is reported. Early identification and management of depression is important to optimise growth outcomes.